Overview on grassland and farming systems in Evros regional unit - Kyriazopoulos A.P.; Manousidis T. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Agriculture is the most important activity of the economy in Evros regional unit followed by livestock farming. Arable land covers 42.35% of the total area. The main cultivation is sunflower representing around 50% of the total production in Greece. Forage crops production is limited and consists mainly of alfalfa. Livestock usually graze at natural and semi-natural grasslands and woodlands. Inappropriate grazing management due to the lack of grazing management plans led to overgrazing or land abandonment. High yielding forage crops are necessary to provide the animal feed. An essential increase in artificial pastures cultivated with drought-resistant grasses and legumes will be a step to combine agricultural and livestock production. Grassland management plans are important in order to sustain grassland and woodland ecosystems and to increase livestock production.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)